Simulation of large-scale ice-sheet surges: The ISMIP HEINO experiments - Greve, Ralf; Takahama, Ryoji; Calov, Reinhard
The three-dimensional, dynamic/thermodynamic ice-sheet model SICOPOLIS (SImulation COde for POLythermal Ice Sheets) is applied to the ISMIP HEINO (Ice Sheet Model Intercomparison Project-Heinrich Event INtercOmparison) set-up. ISMIP HEINO has been designed to study large-scale ice-sheet instabilities, similar to those of the Laurentide ice sheet which are likely the cause of Heinrich events, on a simplified geometry which consists of a flat square with 4000 km side length. This square contains an area which resembles Hudson Bay and Hudson Strait, on which rapid sediment sliding can occur. The ice sheet is built up over 200 ka by assuming a temporally constant glacial climate. For the standard set-up of ISMIP HEINO, we obtain an oscillatory behaviour of the ice sheet with a main period of approx. 7.5 ka. One cycle consists of a gradual growth phase, followed by a massive surge through "Hudson Bay" and "Hudson Strait" owing to rapid sediment sliding on a molten bed. The occurrence of internal oscillations is robust against moderate variations of the surface boundary conditions and the strength of the sediment sliding. These findings support the idea of a free oscillatory mechanism as the main cause for large-scale ice-sheet surges.